(untitled) (Dhaka University Journal of Biological Sciences, 2013)
D21S11 is one of the core short tandem repeat (STR) locus included in most of the commercial kits used for DNA parentage testing, kinship analysis and human identification purpose. It is a complex tetranucleotide repeat located on the long arm of chromosome 21 which surrounds a constant 43 bp section. The allele designation of a particular locus is correctly assigned by comparing the alleles with an allelic ladder that consists of all possible alleles at that particular locus. In this study we observed a variant allele at D21S11 during a routine paternity test while typing the putative father. The variant allele was called by the Genotyper™ software as 34.1, though this allele was not included in the allelic ladder provided by the manufacturer. Sequencing analysis revealed that the variant allele was generated as a change in the repeat motif (TCTA) for TCA at the 3’ end of the repeat region. This variant allele was first reported in Bangladeshi population from our laboratory in a previous report. This study involves further characterization of the reported allele by means of direct DNA sequencing of the D21S11 locus. Dhaka Univ. J. Biol. Sci. 22(2): 85-90, 2013 (July)